Strategi Dakwah Bil Lisan Gus Iqdam Dalam Meningkatkan Religiusitas Mad’u Melalui Majelis Ta’lim Sabilu Taubah - Aisyatul Mubarokah; Alif Albian; Andhita Risko Faristiana (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Da’wah is an obligation of every Muslim that must be carried out continuously, which aims ultimately to change human behavior based on the right knowledge and attitude. Starting from the presence of the Prophet Muhammad SAW who was sent to the earth and began his da’wah for the first time.  Da’wah activities are often interpreted in a narrow sense. Along with the times, in the 21st century there has been a globalization syndrome.   A new taklim assembly known for its success in garnering public attention is Sabilu Tawbah. The Taklim Assembly has a congregation of 2875 members and is recorded up until the beginning of 2022. This research uses descriptivequalitative method.This accomplishment cannot be separated from the duties of a da'i and a taklim assembly supervisor. In Karanggayam Village Srengat District, Blitar Regency, he is Agus Muhammad Iqdam, a youthful preacher and NU leader. Gus Iqdam does more than just preach; he also pays attention to certain elements that are necessary for a da'i to succeed, such as the rhetorical elements of ethos (hikmah), pathos (al-mau'idah hasanah), and logos ('al-Jidal billati hiya ahsan). Which of these three has the greatest impact on a person's level of religiosity?